Attentional Bias and Training in Individuals With High Dental Anxiety - Siev, Jedidiah; Behar, Evelyn; Fortune, Meghan R. (Frontiers in Psychology, 2020)
Dental anxiety is common and associated with negative outcomes. According to information-processing models, anxiety is maintained by maladaptive patterns of processing threatening information. Furthermore, attention training interventions can reduce anxiety in one session. 53 individuals with high levels of dental anxiety completed a Posner reaction-time task. Participants were randomized to attention training or control using a dot-probe task, and then attentional bias was re-measured using another Posner task. Results indicated that individuals high in dental anxiety exhibit threat-relevant attentional bias. There was mixed evidence about the efficacy of attention training. On the one hand, training did not eliminate attentional bias and training condition did not predict distress during the imagery task. On the other hand, cue dependency scores in the control group were higher for dental than neutral cues, but did not differ in the training group. In addition, cue dependency scores for both dental and neutral cues predicted subjective anxiety in anticipation of an imagery task. The mixed results of training are considered in terms of the possibility that it enhanced attentional control, rather than reducing bias.